Effects of Azospirillum isolates isolated from paddy fields on the growth of rice plants - Hossain, Md. Mozammel (Research in Biotechnology, 2015)
Inoculation study in pot culture showed that Azospirillum inoculation could significantly increase all the plant growth parameters including germination. To observe the plant growth promoting effects of Azospirillum isolates, ten isolates collected from North Bengal were used to inoculate Ã¢â‚¬Å“BRRI dhan-28Ã¢â‚¬Â seeds. Inoculated rice seeds were germinated on petri dish and compared with control. Both inoculated and controlled germinated rice seeds were sown in the soil earthen pots. Some plant growth parameters were considered and compared with control. All of the isolates inoculation increases rice seed germination (%) compared to control. Inoculation with most of the isolates showed that Azospirillum inoculation could significantly increase the growth in terms of height, no. of leaf/plant, length and breadth of leaf and fresh and dry weight/plant of rice plant.